Cationic amino acid transporters play key roles in the survival and transmission of apicomplexan parasites - Esther Rajendran (Nature Portfolio, 2017)
Apicomplexans are parasites that use membrane transporters to scavenge essential nutrients from the host. Here the authors identify and characterize two apicomplexans transporters showing that these are crucial for cationic amino acid uptake, parasite survival and virulence.